2020
DOI: 10.1128/iai.00088-20
|View full text |Cite
|
Sign up to set email alerts
|

The ESX-1 Virulence Factors Downregulate miR-147-3p in Mycobacterium marinum-Infected Macrophages

Abstract: As important virulence factors of Mycobacterium tuberculosis, EsxA and EsxB not only play a role in phagosome rupture and M. tuberculosis cytosolic translocation but also function as modulators of host immune responses by modulating numerous microRNAs (miRNAs). Recently, we have found that mycobacterial infection downregulated miR-148a-3p (now termed miR-148) in macrophages in an ESX-1-dependent manner. The upregulation of miR-148 reduced mycobacterial intracellular survival. Here, we investigated miR-147-3p (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
(93 reference statements)
1
9
0
Order By: Relevance
“…The upregulation of miRNA155 inhibits autophagy, which favors Mtb survival in mouse macrophages and human dendritic cells [ 143 , 145 ]. Either the purified EsxA or Mm infection downregulate miR-148 or miR-147 in mouse macrophages, which increases Mm intracellular survival, suggesting that EsxA increases Mm intracellular survival by inhibiting the two miRNAs [ 146 , 147 ].…”
Section: Current Understanding Of Esxa’s Role In Mycobacterium–host Interactionmentioning
confidence: 99%
“…The upregulation of miRNA155 inhibits autophagy, which favors Mtb survival in mouse macrophages and human dendritic cells [ 143 , 145 ]. Either the purified EsxA or Mm infection downregulate miR-148 or miR-147 in mouse macrophages, which increases Mm intracellular survival, suggesting that EsxA increases Mm intracellular survival by inhibiting the two miRNAs [ 146 , 147 ].…”
Section: Current Understanding Of Esxa’s Role In Mycobacterium–host Interactionmentioning
confidence: 99%
“…For instance, a study from Liu et al demonstrated that miR-147 overexpression in macrophages could dampen TLR activation-induced cytokine production in vitro [26]. Furthermore, a recent study demonstrated that virulent factor from the Mycobacterium marinum downregulated miR-147 levels and overexpression of miR-147 dampened Mycobacterium marinum-induced cytokine production in murine macrophage cell lines in vitro [28]. These studies imply the functional role of miR-147 during infection and inflammatory stimulations in macrophages, and potentially other myeloid cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the functional role of miR-147 in many physiological processes including cell cycle regulation and metabolism [25][26][27][28][29][30][31][32]. Here, the expression pattern of miR-147 across different cells and organs is investigated by RT-qPCR.…”
Section: Mir-147 Expression In Different Cell Lines Primary Cells Amentioning
confidence: 99%
See 1 more Smart Citation
“…miR-147-3p expression is modulated by the ESAT-6 secretion system-1 (ESX-1) to mediate the secretion of VFs [ 69 ]. A previous study has shown that the secretion of VFs was mediated by ESX-1, which can aid M. tuberculosis to penetrate the phagosome membrane and translocate into the cytoplasm [ 70 ].…”
Section: Introductionmentioning
confidence: 99%